A performance do Quinteto da Paraíba: entre a cultura musical do Nordeste e outros universos musicais - Sousa, Xisto Medeiros de (2023)
The general objective of this research was to understand how the performance of Quinteto da Paraíba puts different musical elements from Northeast culture into dialogue and interaction with musical aesthetic-sound aspects from other cultural contexts, based on the Group's solo albums. Methodologically, the research is configured as qualitative, with the adoption of data collection instruments, bibliographic research, audio-sound-documentary research, documentary research, and also the participant observation method. The results indicate that the Quinteto da Paraíba constituted its repertoire and, above all, its performance, creating a unique sound identity markedly located in the geographic space of the Brazilian Northeast. The data presented particularities and cultural traits that define the artistic trajectory of the Quinteto da Paraíba and its interrelationships with the musical culture of the Northeast, such as the choice of repertoire registered in the inserts of the discs, with the majority presence of composers from the Northeast; in the motivation for changing the name of Quinteto Ravel to Quinteto da Paraíba; in the interweaving with the Armorial Movement, among other facts. Starting from this point of intersection between the trajectory of Quinteto da Paraíba – the cultural recognition of social groups excluded from the great massification imposed by the media and the need to rescue the identity of a people that increasingly distances itself from its origin – and ethnomusicology, with the research we were able to understand how the cultural miscegenation was determinant in the artistic performance of this group.